PENGENDALIAN MOBILITAS PENDUDUK YANG BERWAWASAN KEBIJAKAN KEPENDUDUKAN NASIONAL DAN TIDAK MELANGGAR HAK ASASI MANUSIA - I Ketut Sudibia (PIRAMIDA, 2005)
For approximately last two decades, on one hand, the number of transmigrates originally from Bali was decline sharply., i.e. from 56.351 persons in the period of 1979-1983 to 17.298 persons in the period of 1994/95-1997/98. On the other hand, in the relatively same period, the number net migration was increase sharply, from (-) 3,1 thousand persons in the period of 1980-1985 to (+) 87,2 thousand persons in the period of 1995-2000. The rapid flow of immigrants to Bali has caused some problems, though it is admitted that their arrival is also give a positive affect, both for the place of origin and the place of destination. Besides emerged from inter provincial migration, problem caused by inter regency migration seems to be critical and have to be overcame soon in the regional autonomy era. The strategy carried out has to be based on national demography policy, especially in relation with Undang-Undang No. 10, 1992 about ?Population Growth and Development of Wealthy Family?, and Undang-Undang No. 39, 1999 about ?Human Right?. Based on those regulations, it is stated that government not able to prohibit resident to do both inter provincial and inter regency mobility, because every resident have right to chose their residence and job according to their wish. Population mobility is a natural life phenomenon and inevitable due to rapid improvement of communication technology. Every region has to recognize supporting and capacity powers of their regional environment. Particularly to the place of destination, it is important to know about the amount and qualification migrant labor need. Through this kind of mobility, presence of migrant in the place of destination will complimentary to social and economic life of the place of origin. Such a condition, not only be able to prevent conflict between migrants and local resident, but also smoothing national integration process. Besides rights for doing mobility, one thing has to be remembered by all resident (including migrant), is obligation to obey and follow population regulation, both at the place of destination and the place of origin.